The Effect of Managerial Supervision on School Supervisors, Competence, and Achievement Motivation on The Performance of Primary School Principals at The Dikbud Office Kec. Adiwerna Kab. Tegal - Emgiek, Rina Agustina; sutarto, Joko; Prihatin, Titi (Educational Management, 2018)
The background of the problem in the study, although through Supervisory supervision of the school but the performance of Principals in running TUPOKSI not optimal, not all Principals realize the importance of motivation so that the performance of the work is still limited, and the need for a combination of Supervisory school, competence and motivation of Principal Primaryto improve the performance so that the assessment result is not fluctuate and tends to decrease. The purpose of this study is to examine the influence of Supervisory supervision on performance, to test the influence of competence to performance, to test the influence of achievement motivation toward performance, and to test the influence of Supervisory supervisor, competence and achievement motivation toward Principal.